PEMETAAN KERAWANAN TSUNAMI DI KECAMATAN PELABUHANRATU KABUPATEN SUKABUMI - Bayu Surya Pramana (Sosio Didaktika: Social Science Education Journal, 2015)
Pelabuhanratu sub-district located in the southern part of West Java has the tsunami disaster vulnerability is high, because the South region of West Java directly adjacent to the zone plate’s movement and in the Indian Ocean. So that this region is very vulnerable to an earthquake that occurred under the sea, earthquake phenomenon is largely a high potential for the occurrence of the tsunami disaster. This article will explain the vulnerability of the tsunami in the District Pelabuhanratu, through the application of GIS and field survey which will be known the factors causing the high value of the vulnerability, the potential damage, and tsunami evacuation locations in District Pelabuhanratu. Subdistrict Pelabuhanratu indicate that value or category of vulnerability tsunami in the District Pelabuhanratu dominated by the 46% category Rawan, Rawan Enough 19% and 17% Highly Prone. With these conditions, the District of Pelabuhanratu categorized as tsunami-prone area.   Permalink/DOI: http://dx.doi.org/10.15408/sd.v2i1.1383